1990
DOI: 10.1029/jd095id04p03599
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of tropospheric ozone determined from satellite data

Abstract: An analysis of more than 22,000 ozone profiles from Stratospheric Aerosol and Gas Experiment I (SAGE I) (1979–1981) and SAGE II (1984–1987) between 50°N and 50°S is used in conjunction with 9 years (1979–1987) of daily global depictions of total ozone from the Total Ozone Mapping Spectrometer (TOMS) instrument aboard Nimbus 7 to investigate the spatial distribution and seasonal cycle of the integrated amount of ozone in the troposphere. In the tropics, highest concentrations are found in the eastern Atlantic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
280
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(300 citation statements)
references
References 38 publications
19
280
0
1
Order By: Relevance
“…As a consequence of the photochemical oxidation of these tracers elevated 03 mixing ratios were measured (Smit et al, 1990). These results also agree with the data published by Fishman et al (1990), who reported tropospheric ozone distributions determined from satellite data between 1979 and 1987. For the period September to November, they found an area of significantly elevated 0 3 mixing ratios over the mid-Atlantic between 5°Sand 25 0 S.…”
Section: The Latitudinal Distribution Ofethanesupporting
confidence: 82%
See 1 more Smart Citation
“…As a consequence of the photochemical oxidation of these tracers elevated 03 mixing ratios were measured (Smit et al, 1990). These results also agree with the data published by Fishman et al (1990), who reported tropospheric ozone distributions determined from satellite data between 1979 and 1987. For the period September to November, they found an area of significantly elevated 0 3 mixing ratios over the mid-Atlantic between 5°Sand 25 0 S.…”
Section: The Latitudinal Distribution Ofethanesupporting
confidence: 82%
“…South of the equator, the NMHC patterns changed again and tracers of biomass burning such as acetylene, CO, and ethane increased over a latitude range of about 10°followed by a decrease towards increasing southern latitudes. This region of enhanced long-lived NMHC coincides in season and location with the area of elevated tropospheric ozone observed by Fishman et al (1990). Since the pattern of the NMHC and other trace gases indicate aged biomass burning emissions, this supports the assumption that this area of increased tropospheric ozone is due to biomass burning.…”
Section: Discussionsupporting
confidence: 67%
“…The Fortuin and Kelder (1998) climatology is reported in volume mixing ratios (vmr) for specific pressure levels. In order to convert the volume mixing ratios (ppm) at the ith level to Dobson units (DU), the following formula was used, taking into account the ideal gas law and the horizontal surface density (Ziemke et al, 2001): Cor ACCO …”
Section: The Ccd Methodsmentioning
confidence: 99%
“…Tropospheric ozone was first retrieved from space with the so-called residual method. The stratospheric ozone column above 100 mbar retrieved from the Stratospheric Aerosol and Gas Experiment II (SAGE II) was subtracted from the total ozone column (TCO) retrieved from the Total Ozone Mapping Spectrometer (TOMS) aboard the Nimbus 7 satellite (Fishman et al, 1990). The following years several other methods have been developed, such as the cloud slicing (CS) technique (Ziemke et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although global observations of tropospheric O 3 , carbon monoxide (CO) and nitrogen dioxide (NO 2 ), the latter being important O 3 precursors, have recently become available from satellite-based observations (Fishman et al, 1990;Borrell et al, 2003;Deeter et al, 2004;Buchwitz et al, 2004), the measurements are generally not vertically resolved and refer to cloud-free conditions only, which limits their representativeness. Additionally, satellite retrievals must be validated against independent remote sensing or in-situ data.…”
Section: Introductionmentioning
confidence: 99%